How great is current curative expenditure and catastrophic health expenditure among patients with cancer in China? A research based on "System of Health Account 2011". (20th June 2018) - Zheng, Ang; Duan, Wenjuan; Zhang, Lin; Bao, Xintong; Mao, Xiaoyun; Luo, Zhuojun; Jin, Feng
Abstract: In recent years, the incidence and mortality of cancer have witnessed a dramatic increase. Cancer has already caused severe economic burdens on society, especially in developing countries and has become a major public health concern. This study evaluates the medical economic burden, including total current curative expenditure (CCE) and catastrophic health expenditure (CHE) on cancer in Liaoning Province, China. A total of 252 medical institutions were investigated with multistage stratified cluster random sampling. We established a standardized database of 3 532 517 samples. "System of Health Account 2011", a new internationally recognized accounting system, was established to analyze the CCE on six most common cancers. CHE were estimated from the extracted 1344 patients with cancer, which performed a cross‐sectional study. The association of individual and contextual factors with CHE was evaluated using logistic regression models. CCE for all the patients with the six types of cancer was 2801.38 million CNY in Liaoning Province, the highest of which was lung cancer. The incidence of CHE was 42.78%, while the threshold was 40%. The average and relative distance were 10.41% and 24.32%, respectively. Influencing factors were length of stay, type of health insurance, location of household, etc. Our findings highlight the need to address medical economic burden in the cancer population. Households with the cancer are more likely to incur CHE. Financial intervention to prevent it should target on poor households. We provide suggestions in aspects of health insurance and health service management to reduce CHE. Abstract : Based on a multi‐center of 3 532 517 cases in China, the study adopted "System of Health Accounts 2011" to calculate current curative expenditure of six most common cancers and estimate catastrophic health expenditure among patients with cancer. Our findings highlight the need to address medical economic burden in the cancer population.